2015
DOI: 10.3390/land4010045
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Forest Cover Change with Census Data: Drivers and Contexts from Bolivia and the Lao PDR

Abstract: Abstract:The aim of this paper is to explore possible links between forest cover change and characteristics of social-ecological systems at sub-national scale based mainly on census data. We assessed relationships between population density, poverty, ethnicity, accessibility and forest cover change during the last decade for four regions of Bolivia and the Lao PDR, combining a parcel-based with a cell-based approach. We found that accessibility is a key OPEN ACCESSLand 2015, 4 46 driver of forest cover change,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…In recent years, several spatial and spatio-temporal assessments of land change have been carried out on different scales relevant to Laos. These include an assessment of land cover change for Montane Mainland South East Asia MMSEA on the regional level (Fox et al, 2012;Fox & Vogler, 2005;Leinenkugel et al, 2015) an inventory of land cover mosaics on the national level by Messerli et al (2009), several assessments of shifting cultivation using remote sensing on the subnational level (Boillat et al, 2015;Hurni et al, 2013;Hurni, et al 2012;Kamusoko et al, 2013;Liao et al, 2015) and effects of specific crops on landscapes and livelihoods on the local level (Evans et al, 2011). While the more local studies depict the agricultural transitions clearly, the transitions are not as evident from the large scale assessments as there is only a focus on land cover changes, ignoring the intricate changes in the land systems of which land cover change studies only provide a partial reflection (Schmidt-Vogt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several spatial and spatio-temporal assessments of land change have been carried out on different scales relevant to Laos. These include an assessment of land cover change for Montane Mainland South East Asia MMSEA on the regional level (Fox et al, 2012;Fox & Vogler, 2005;Leinenkugel et al, 2015) an inventory of land cover mosaics on the national level by Messerli et al (2009), several assessments of shifting cultivation using remote sensing on the subnational level (Boillat et al, 2015;Hurni et al, 2013;Hurni, et al 2012;Kamusoko et al, 2013;Liao et al, 2015) and effects of specific crops on landscapes and livelihoods on the local level (Evans et al, 2011). While the more local studies depict the agricultural transitions clearly, the transitions are not as evident from the large scale assessments as there is only a focus on land cover changes, ignoring the intricate changes in the land systems of which land cover change studies only provide a partial reflection (Schmidt-Vogt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Easily accessible communes inhabited by ethnic majority groups (Kinh) have increased forest cover. Similar situations have been found in Luang Prabang Province, Lao PDR, where forest gains that have occurred in more accessible areas shed further light onto the interaction between accessibility and other land use change drivers (Boillat et al ., ). Unlike the above studies, Do () reported that the key controlling factor of forest change in Vietnam's mountainous regions was the increasing demand of forestlands for cash plantations, namely, coffee and rubber.…”
Section: Resultsmentioning
confidence: 97%
“…In using the classification, it has to be kept in mind that it is a diagnostic, descriptive assessment of one snapshot in time. As Boillat et al (2015) mentioned, meso-scale analyses are not capable to make statements about details of local conditions but they can lay out the scope of contexts for studies at finer scales. This typology can, therefore, be the basis for systematic selection of case study sites for more specific analyses e.g.…”
Section: Land Systems Classificationmentioning
confidence: 99%
“…Assessing land systems becomes especially critical at scales above the sub-national level (Boillat et al, 2015;Messerli, Bader, Hett, Epprecht, & Heinimann, 2015;Schmidt-Vogt et al, 2009). At these larger spatial scales land cover data often becomes aggregated to larger units, while losing the mosaic of different, functionally important land use and land cover types (Verburg et al, 2011).…”
Section: Introductionmentioning
confidence: 99%